The Anterior Lateral Decubitus Intermuscolar and the Postero-Lateral approaches in total hip arthroplasty: a comparative study - Niccoli, Giuseppe; Bozzi, Federico; Candura, Dario; Damiani, Luca; Perticarini, Loris; Li Bassi, Giovanni; Terragnoli, Flavio (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Recently a modification of the DAA in lateral decubitus, called ALDI, has been proposed to obtain a better surgical exposure and to facilitate surgeons accustomed to the other hip approach. In this paper we report our early experience with the ALDI approach for total hip arthroplasty (THA) and to compare outcomes between ALDI and posterolateral approach (PLA) in a retrospective investigation.Methods: We have identified THA performed from September 2017 to January 2020. We collected patients demographic, clinical and radiographic data by our electronic hospital database. The ALDI group included 60 hips and the PLA group included 219 hips. These patients underwent to strict follow-up in the first 3 post-operative months.Results: Compared to the PLA, the ALDI approach showed clinical outcomes significantly higher in the first month of follow-up. The PLA group has a lower operative time and a greater mean hospital length of stay. No blood transfusions were administered in the ALDI group while the 1.4% of patients in the PLA group needed blood transfusion. Cup anteversion and inclination angles were significantly wider in the PLA group. THA dislocation occurred in seven patients of the PLA group. No femoral cutaneus nerve palsy was recorded in the ALDI group.Conclusions: The ALDI approach can represent a quickly and safe solution for surgeons who are accustomed to the PLA who want to perform THA in DAA. Our preliminary experience is encouraging in terms of clinical and radiographic parameters although the operative time needs to be improved.